Modelling the relationship between green marketing strategies and performance outcomes for business sustainability - Hasan, Zuhairah; Ali, Noor Azman (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This article presents an integrative model on how the commitment of a green industry can give impact to the economic, marketing and environmental performance. The issues become pertinent to the global as it influences the way business practice as it gives detrimental impact to the economy, environment and society. Since many firms are converting to green industry business, the challenge is to ensure the strategy adopted can contribute to the organizational performance. More firms are aligning their activities with the principles of sustainable development. While interest in, and proactive commitment to aligning their business activities to achieve sustainable development, this paper addresses several issues in the green marketing strategies. This article empirically examines on how green marketing strategies influence different dimensions on organizational performance among the ISO 14001 certified firms in Malaysia. This study uses a structured questionnaire derived from the literature and employing a mail survey and distributed to 100 respondents and it reports the empirical results of a survey. The results of testing the hypotheses that predicted that green product, green price, green promotion, green distribution, strategic competency and marketing resources significantly positively affects organizational performance. Management implications to re-orient their marketing strategies are discussed.